Acute biliary pancreatitis: the evolution of surgical tactics (review of literature) - T. O. Nikitina; D. N. Popov; A. U. Korolkov; S. F. Bagnenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Surgical treatment of acute biliary pancreatitis over the past decades have been improved from realization of open traumatic surgical interventions to the use of minimally invasive technologies. However, despite the progress in the treatment of this pathology, the question of the timing of cholecystectomy after endoscopic papillosphincterotomy with lithoextraction remains unresolved. In some cases, after the endoscopic papillosphincterotomy, a recurrence of the disease occurs, as well as other various biliary complications, such as: acute calculous cholecystitis, choledocholithiasis, cholangitis, associated with the fact that the main etiological factor – the gallstone disease – has not been eliminated, specifically, cholecystectomy was not performed.The objective of this study was to analyze the evolution of surgical tactics in the treatment of acute biliary pancreatitis with combined cholecystocholedocholithiasis.